Application of the Correlation Velocity Measurements for Hydrodynamic Investigations of Turbulent Coolant Flow in Nuclear Reactor Elements - I. A. Konovalov; A. E. Khrobostov; M. A. Legchanov; D. N. Solncev; A. A. Barinov; A. V. Ryazanov; A. A. Chesnokov; M. A. Makarov (Приборы и методы измерений, 2020)
The method of correlation measurement of the coolant flow rate, widely used for operational diagnostics of nuclear power plants, can be extensively used in research practice. The aim of this work was to apply a correlation method based on the conductometric measurement system with wire-mesh sensors for measuring a coolant flow rate.Insignificant concentration of a salt solution (NaCl or Na2SO4 ) creates a gradient of the conductivity in the flow, which is used as a passive scalar measured by the system. Authors used turbulent pulsations at the interface of two concurrent flows with identical velocities in a square channel as a signal source for the correlation method. The paper presents the methodology of the tests, test facility description, signalto-noise ratio estimation, the results of digital signal processing and comparison of the measured velocities in the model with the flowrate‒averaged velocity determined by the use of flowmeters. The measured velocity values give acceptable agreement for the turbulent flow modes. It was shown that the measurement accuracy drops sharply for low-Reynolds flows.The obtained results were used for flowrate measurements in core-imitator channels of the nuclear reactor test model. The presented paper is an approbation of this approach for its application as part of an test model of a nuclear reactor in order to determine the each duct flow rates in the channels of the core simulator using wire mesh sensors.